A numerical investigation of the flow around a plate impinged in two dimensional free jet flow - Eren, H; Peremeci, ÖE; Dagtekin, I (Begell House, Inc, 1999)
In this study, the flow field around a plate placed within the free jet flow is investigated numerically. The plate can be placed perpendicularly as well as parallel to the jet direction. The finite difference equations are obtained by applying the Crank-Nicholson implicit method to the non-dimensional equations of motion for the unsteady now of the compressible fluid; and the flow behavior around the plate is investigated by solving those equations for Re=30 with a computer program coded in Fortran TI.
2nd Trabzon International Energy and Environment Symposium -- JUL 26-29, 1998 -- KARADENIZ TECH UNIV, TRABZON, TURKEY
Keywords: Turbulent